2013
DOI: 10.1111/psyp.12148
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac stability at differing levels of temporal analysis in panic disorder, post‐traumatic stress disorder, and healthy controls

Abstract: The panic disorder (PD) literature provides evidence for both physiologic rigidity and instability as pathognomonic features of this disorder. This ambiguity may be a result of viewing PD at differential levels of temporal analysis. We assessed cardiac variability across three levels of temporal scale in PD patients, posttraumatic stress disorder (PTSD) patients, and healthy controls. Sixteen healthy controls, 14 PD patients, 23 PTSD patients, and 16 PTSD+PD patients presented for a polysomnogram. Differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
31
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
(77 reference statements)
2
31
0
1
Order By: Relevance
“…A previous study reported that anxiety disorders are associated with significantly lower HRV but that the association is mainly driven by the effects of antidepressants, such as tricyclic antidepressants and selective serotonin reuptake inhibitors,43,57 which decrease vagal activity and alter vagal outflow 19,57,58. Previous studies have also shown that benzodiazepines can influence autonomic neurocardiac regulation, reducing central vagal tone, possibly through their interaction with the gamma-aminobutyric acid-A receptor chloride ion channel complex 59.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that anxiety disorders are associated with significantly lower HRV but that the association is mainly driven by the effects of antidepressants, such as tricyclic antidepressants and selective serotonin reuptake inhibitors,43,57 which decrease vagal activity and alter vagal outflow 19,57,58. Previous studies have also shown that benzodiazepines can influence autonomic neurocardiac regulation, reducing central vagal tone, possibly through their interaction with the gamma-aminobutyric acid-A receptor chloride ion channel complex 59.…”
Section: Discussionmentioning
confidence: 99%
“…The present study only uses the data on heart rate (HR) and respiratory sinus arrhythmia (RSA). Complete details regarding recruitment procedures, screening, diagnostic interviewing, and physiological data collection and methodology (including electrocardiography signal cleaning and preparation) are published in the study by Fisher and Woodward (22). The present sample comprised 69 individuals, 16 healthy controls, 23 individuals with PTSD, 14 individuals with panic disorder, and 16 individuals with co-occurring PTSD and panic disorders.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the sampling rate of the measurements and the temporal scale of the data analysis will come to bear on the conclusions (c.f. Fisher & Woodward, 2014). …”
Section: Rigidity Flexibility and Instabilitymentioning
confidence: 99%
“…Flexibility, rigidity, and stability are popular constructs that have been employed across various psychological research domains, including psychotherapy (Newman & Fisher, 2013), psychophysiology (Fisher & Woodward, 2014; Hoehn-Saric, McLeod, Funderburk, & Kowalski, 2004), personality (Wright, Pincus, & Lenzenweger, 2012), and emotion regulation (Gruber, Kogan, Quoidbach, & Mauss, 2013). Yet, inconsistencies remain in the operationalization and quantitation of these constructs, and it is not always clear where the distinctions lie between instability and flexibility, or stability and rigidity.…”
mentioning
confidence: 99%